PENENTUAN CIRI-CIRI PLAGIARISME DALAM MAKALAH ILMIAH YANG MEREFERENSI SUMBER DALAM BAHASA ASING YANG DITERJEMAHKAN - Michael Iskandar (Bina Ekonomi, 2009)
Whenever lecturers assign their students to write scientific papers they must be alert to the plagiarism problem. While a lot has been written about plagiarism, particularly by university policymakers, none address the problem when a student paraphrases and translates one or more passages from sources written in a foreign language. This paper strives to find an answer whether this form of plagiarism or not.  In particular, the research strives to find the answer of the following question: what are the characteristics of plagiarism between languages?. Preliminary and superficial research has shown that there are three main aspects that many sources address; the definition of plagiarism, the types of plagiarism, and the characteristics of plagiarism. This research is then done by studying and compiling from those various sources, and then analyzing each aspect separately. To these was added an analysis on the ethical principles that underlie human behavior, with which the insistence  that plagiarism  is wrong may be validated.  The conclusions of this research  are  that  (a) plagiarism  is most strongly described as a kind of fraud, not a kind of theft; (b) none of the ethical principles evaluated separately  is strong enough to deter plagiarism; (c) there are types of plagiarism  that aren't relevant  in a discussion  on undergraduate  scientific paper writing; and (d) if a translated passage  is translated  back  into its original  language, and the  result  is the same or very similar to the original text,  then plagiarism  has occurred.